REGULASI EMOSI DITINJAU DARI PERILAKU PROSOSIAL PADA SISWA SMA RAKSANA DI MEDAN - siska friskica hutahaean (Jurnal Psikologi Universitas HKBP Nommensen, 2020)
This research purpose is to get to know the relation between the emotion regulation and the prosocial behavior. The hypothetical that submitted in the research is about the positive relation between the emotion regulationand prosocial behavior, that assumption is the higher emotion regulationthan the prosocial behavior is also getting high, otherwise the lower emotion regulation then the prosocial behavior is getting low either. The subject research which used in this investigation is 177students in Raksana Hight School Medan. The data obtained based on scale to measure the emotion regulationwith the prosocial behavior. The calculation has done by prerequisite analysis test (assumption test) which consists of the normality distribution test and the relation of linearity. The data analysis used is using the Product Moment correlation through the SPSS 19 aid for Windows. The data analysis result showed the coefficient correlation 0,456 (p < 0,05). It showed positive relation between emotion regulationand the prosocial behavior. This investigation showed contribution statistical psychological capital variable toward job satisfaction is 20,8 percent, the rest 79,2 affected by other factors which not examined. The result of this study can be concluded that the hypothesis research has positive relation between the emotion regulationand prosocial behavior acceptable.